Originally Posted by

**Mathstud28** $\displaystyle x^2e^{-x}\$=$\displaystyle \sum_{n=0}^{\infty}(-1)^{n}\frac{x^{n}}{n!}\$$\displaystyle x^2\$

and if you put in $\displaystyle \sum_{n=0}^{10}(-1)^{n}\frac{x^{n}}{n!}\$$\displaystyle x^2\$ you get.048675 and if you input $\displaystyle \frac{1}{4}\$ into $\displaystyle x^2e^{-x}\$ you get the same answer

and if you really wanted to be good you could distribute and get $\displaystyle x^2e^{-x}\$=$\displaystyle \sum_{n=0}^{\infty}(-1)^{n}\frac{x^{n+2}}{n!}\$